Comparison of the effects of an intravenous lidocaine infusion combined with 1% isoflurane versus 2% isoflurane alone on selected cardiovascular variables and recovery characteristics during equine general anaesthesia. (January 2017) - Cruz Benedetti, Inga-Catalina; Nottrott, Knut; Fourel, Isabelle; Le Bris, Marjolaine; Mongellas, Emilie; Portier, Karine
Abstract: Objectives: To compare the effects of a lidocaine constant rate infusion (CRI) combined with 1% isoflurane versus those of 2% isoflurane alone on cardiovascular variables in anaesthetized horses, and to estimate the sample size required to detect a difference in recovery quality. Study design: Prospective, randomized, blinded, crossover study. Animals: Twelve healthy experimental horses. Methods: Horses were anaesthetized twice using an intravenous (IV) administration of acepromazine, romifidine, diazepam and ketamine. Horses were placed in dorsal recumbency and ventilated mechanically. During the first 10 minutes (P1), anaesthesia was maintained with a 2% inspired isoflurane fraction (FIIso). During the following 20 minutes (P2), horses received IV lidocaine (1.5 mg kg −1 ) (group IL) or saline (group I). During the last 60 minutes (P3), group IL received a lidocaine CRI (50 μg kg −1 minute −1 IV) and FIIso 1%, whereas group I received a saline CRI and FIIso 2%. Three weeks later, the horses received the alternative treatment. Painful stimuli were induced by introducing an 18 gauge needle intramuscularly. Ketamine and dobutamine requirements and physiological variables were recorded. Recoveries were assessed by two anaesthetists unaware of the treatment. Lidocaine plasma concentrations were measured during recovery. Data were analysed withanova . Results: During P3, group IL had a lower heart rate ( p  = 0.002), higher mean arterial pressure ( p < 0.001) and lower dobutamine requirement (p < 0.001) than group I. One horse had lidocaine plasma concentrations above toxic levels. Recoveries did not differ significantly between groups. Sample sizes of 208 horses in each group would be necessary to detect a statistically significant difference (85% statistical power) in recovery quality. Conclusions and clinical relevance: A lidocaine CRI combined with FIIso 1% rather than FIIso 2% alone may improve cardiovascular variables in healthy anaesthetized horses.